Effect of heating/reheating of fats/oils, as used by Asian Indians, on trans fatty acid formation. (1st December 2016) - Bhardwaj, Swati; Passi, Santosh Jain; Misra, Anoop; Pant, Kamal K.; Anwar, Khalid; Pandey, R.M.; Kardam, Vikas
Highlights: Formation of trans fatty acids (TFA) occurs during frying/heating of fats/oil. TFAs were estimated in 6 fats/oils before/after heating/frying at 180 °C and 220 °C. Heating/frying led to formation and increase in TFA in all fat/oil samples. Heating/frying also increased the saturated fatty acids and decreased cis -unsaturated fatty acids. Guidelines for heating/re-frying of fats/oils by Asian Indians should be devised. Abstract: Heating/frying and reuse of edible fats/oils induces chemical changes such as formation of trans fatty acids (TFAs). The aim of this study was to investigate the effect of heating/frying on formation of TFAs in fats/oils. Using gas chromatography with flame ionisation detector, TFA was estimated in six commonly used fat/oils in India (refined soybean oil, groundnut oil, olive oil, rapeseed oil, clarified butter, partially hydrogenated vegetable oil), before and after subjecting them to heating/frying at 180 °C and 220 °C. All six fats/oils subjected to heating/frying demonstrated an increase in TFAs ( p < 0.001), saturated fatty acids ( p < 0.001) and decrease in cis -unsaturated fatty acids ( p < 0.001). The absolute increase in TFA content of edible oils (after subjecting to heating/reheating) ranged between 2.30 ± 0.89 g/100 g and 4.5 ± 1.43 g/100 g; amongst edible fats it ranged between 2.60 ± 0.38 g/100 g and 5.96 ± 1.94 g/100 g. There were no significant differences between the two treatment groups (heating and frying; p = 0.892). Considering the undesirable health effects of TFA, appropriate guidelines for heating/re-frying of edible fats/oils by Asian Indians should be devised.